ATOPIC DERMATITIS: NEW TARGETS OF THERAPY - D. Sh. Macharadze ("Paediatrician" Publishers LLC, 2014)
Treatment of atopic dermatitis (AD) is most often based on the relief of symptoms. Two fundamental basis of AD - dry skin and itching - determine the main objectives of treatment of this chronic inflammatory diseases of the skin. With this purpose, the patients are recommended to use moisturizers (emollients) and topical anti-inflammatory drugs - corticosteroids, and/or calcineurin inhibitors. However, there are studies conclusively proving the existence of subclinical inflammation associated with impaired barrier function ofthe skin, production of cytokines and infiltration of lymphocytes. The new strategy of treatment - proactive therapy aimed at achieving control and maintenance of remission of atopic dermatitis. This will allow you to achieve faster control the symptoms of AD and to reduce the risk of recurrence of the disease.